2015
DOI: 10.1007/s11010-015-2510-3
|View full text |Cite
|
Sign up to set email alerts
|

Exon array analysis reveals genetic heterogeneity in atypical femoral fractures. A pilot study

Abstract: Atraumatic subtrochanteric and diaphyseal (atypical) femoral fractures are a rare, but important adverse event in patients treated with potent anti-resortive agents. The mechanisms involved are unknown and particularly the association with genetic variants has not been explored. The aim of the study was to identify rare genetic variants that could be associated with the occurrence of these fractures. We performed a genome-wide analysis of up to 300,000 variants, mainly distributed in gene coding regions, in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Although the sample size was very small (13 AFF cases; 268 controls), patients tended to accumulate some rare variants, and consequently the number of risk variants was markedly different between patients and controls. These results suggest that AFF are polygenic in nature, associated with the accumulation of changes in the coding regions of several genes [108 ] . Most genes in the study did not have a well-established relation with bone metabolism.…”
Section: Atypical Femoral Fractures (Aff)mentioning
confidence: 84%
See 1 more Smart Citation
“…Although the sample size was very small (13 AFF cases; 268 controls), patients tended to accumulate some rare variants, and consequently the number of risk variants was markedly different between patients and controls. These results suggest that AFF are polygenic in nature, associated with the accumulation of changes in the coding regions of several genes [108 ] . Most genes in the study did not have a well-established relation with bone metabolism.…”
Section: Atypical Femoral Fractures (Aff)mentioning
confidence: 84%
“…Isolated reports suggest that individuals with rare mutations of the alkaline phosphatase gene (ALPL) may have higher risk of developing AFF when treated with bisphosphonates [107 ] . However, ALPL mutations are very rare among patients with AFF, thus indicating that genetic variants of ALPL are not a major determinant of AFF risk [108,109 ] . There is very little information about the potential involvement of other genes in AFF.…”
Section: Atypical Femoral Fractures (Aff)mentioning
confidence: 99%
“…In a pilot study, Pérez‐Núñez and colleagues conducted an exon array analysis (Affymetrix Axion 2.0 exome array) in 13 women with AFFs and 268 controls that consisted of healthy women ( n = 87) and patients with postmenopausal osteoporosis without AFFs ( n = 181) (Table ). By including the osteoporosis patients in the control group, the investigators intended to avoid the finding of osteoporosis‐related variants rather than variants associated with AFFs.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in CYP1A1 were found in the three sisters and one unrelated patient in our study and also reported elsewhere in two patients with AFF and glucocorticoid‐induced osteoporosis . Another study identified a missense variant in the PPEF2 gene significantly associated with AFF by exon array analysis of a small cohort . To date, this gene has no known function in bone metabolism.…”
Section: Atypical Femoral Fracturementioning
confidence: 99%